2023
DOI: 10.1097/aud.0000000000001338
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intratympanic Steroid and Hyperbaric Oxygen Salvage Therapy Hearing Outcomes in Idiopathic Sudden Sensorineural Hearing Loss: A Retrospective Study

Abstract: Objectives: Systemic steroids are the most common first-line therapy in sudden sensorineural hearing loss (SSNHL), with significant improvement in hearing outcomes in over 60% of patients. It is unknown why 40% of patients do not respond to systemic steroid therapy. Salvage treatment includes intratympanic steroids (ITS) and hyperbaric oxygenation (HBO) therapy, with inconsistent results reported. This study aimed to compare the results of ITS and HBO therapy in patients with SSNHL that previously failed syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Moreover, IPTW can only account for known variables, leaving room for potential bias from unmeasured factors. Previous studies have suggested that ITSI may contribute to hearing improvement, 27 , 37 , 38 , 39 , 40 emphasizing the need for cautious interpretation of our findings in the context of potential uncontrolled confounding. However, the sensitivity analysis comparing PSL alone to HBOT combined with PSL showed a similar trend to the overall analysis, which may indicate the robustness of the present result.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, IPTW can only account for known variables, leaving room for potential bias from unmeasured factors. Previous studies have suggested that ITSI may contribute to hearing improvement, 27 , 37 , 38 , 39 , 40 emphasizing the need for cautious interpretation of our findings in the context of potential uncontrolled confounding. However, the sensitivity analysis comparing PSL alone to HBOT combined with PSL showed a similar trend to the overall analysis, which may indicate the robustness of the present result.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, another meta‐analysis that evaluated 19 observational studies found that the HBOT group exhibited an average hearing improvement of 8.74 dB more than the non‐HBOT group, along with an OR for CR of 1.61. 9 Moreover, despite its role as a salvage treatment, the Ajduk et al 27 retrospective study on hyperbaric oxygen salvage therapy in SSNHL found an average hearing improvement of 7.4 dB at all frequencies (250–8000 Hz). The results of our study, demonstrating an average difference in hearing improvement of 7.6 dB and a higher CR rate with an OR of 2.57, are consistent with those previous findings, reinforcing the validity of our outcomes, although the clinical significance of the HBOT on SSNHL remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, treatment failure still exists and is reported as up to 40% in several reports, although the definition of treatment failure varies. 15 The ITS has been most studied as the salvage treatment of SSNHL, which showed at least a tendency to show better results than control for PTA improvement and/or the recovery rate. A recent meta-analysis reported a mean 11.5 dB improvement of PTA by ITS versus 2.7 dB for placebo.…”
Section: Discussionmentioning
confidence: 99%
“…34 49 Therefore, ischemia-hypoxia and inflammation are thought to be the primary causes of ISSNHL. 13 Hypoxia leads to ciliary fusion of cochlear hair cells, edema of synapses and dendrites, and continuous depolarization. 50 HBOT has been reported to improve ischemia and hypoxia of the inner ear by increasing the oxygenation of the inner ear and the partial oxygen pressure of the perilymphatic fluid.…”
Section: Echanisms Of H Yperbaric O ...mentioning
confidence: 99%
“… 6 12 HBOT is also a kind of important treatment to save hearing loss for patients who have failed steroid therapy. 13 In addition, combining HBOT with traditional steroid therapy was found to be more effective than using steroids alone. 12 Although HBOT has been successfully used as a conventional adjuvant therapy in the treatment of ISSNHL, its exact mechanisms are still unknown.…”
Section: Introductionmentioning
confidence: 99%